Superficial Keratopigmentation: An Alternative Solution for Patients With Cosmetically or Functionally Impaired Eyes. Issue 1 (January 2019) - Al-Shymali, Olena; Rodriguez, Alejandra E.; Amesty, Maria A.; Alio, Jorge L.
Abstract : Purpose: To report the use of different superficial keratopigmentation (KTP) techniques for restoring or enhancing cosmetic appearance of eyes impaired for several reasons. Methods: This is a retrospective, consecutive, noncomparative interventional series of cases, in which 136 cosmetically disabled eyes (due to different corneal abnormalities) of 130 patients were included. A total of 222 procedures of superficial manual KTP and superficial automated KTP were performed. The procedures were divided into 2 groups: first and second-stage procedures. The patients' cosmetic appearance and satisfaction were evaluated and graded as excellent, good, or poor. Results: A total of 222 procedures were performed, 57.2% were superficial automated KTP, 22.5% were superficial manual KTP, and 20.3% included the combination of superficial KTP with other KTP techniques. Six procedures were purely cosmetic, 16 therapeutic functional, and 200 therapeutic cosmetic. Superficial KTP, as a second-stage procedure, was performed in 13 eyes that were previously pigmented by intrastromal techniques. Superficial KTP as an initial indication (first-stage procedure) alone or in combination with another KTP technique in the same surgery was performed in 123 eyes, in which 44.7% of them were reoperated once or more. Best-corrected visual acuity changed insignificantly, and the intraocular pressure decreased significantly in all the studied groups. No intraoperative complications were observed, 11.2% of eyes with a follow-up time of more than 3 months developed postoperative complications. Most of the patients (98.5%) were satisfied. Conclusions: The modern superficial KTP procedure provides the possibility to improve the cosmetic appearance of impaired eyes, as an alternative to evisceration, enucleation, prosthetic contact lenses, or keratoplasty.